Predictors of Irregularities in PMTCT / eMTCT Service Attendances in Samia Bugwe North: Health Facility Study - Busia - Uganda - Francis, WABWIRE Paul; Evarine, NAMPEWO (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
011) and long waiting time (P-value = 0.03) were significantly associated with irregularattendance in the service. The prevalence of irregular attendance (43.75%) was however lower than54% of [13]although, in agreement with [18] who rated maternal adherence to preventive drug regimensat time of delivery that varied widely across sites between 35% and 93.5%.The qualitative section used open-ended in-depth interview. The quotes were used in report tocomplement the findings of quantitative data. The results were that education, distance, economicstatus and male involvement were highly associated with irregularities in PMTCT / eMTCTattendance.